Troubleshooting the implementation of a template to evaluate and record SDF caries arrest - Crystal, Y. O.; Song, S. G.; Saraza Reduta, V.; Majstorovic, M.; Raveis, V. (Frontiers in Dental Medicine, 2025)
PurposeThe aim of this study was to investigate the feasibility of using an electronic note template to evaluate and record caries arrest from the application of 38% Silver Diamine Fluoride (SDF) at the New York University College of Dentistry Pediatric Clinic (NYUCD-PD). The study evaluated adherence to its use and explored barriers and alternatives to document this procedure among the post-doctoral residents.MethodsA template was designed to collect baseline characteristics of treated teeth, application methods, and caries arrest at subsequent visits. The template was implemented among 26 post-graduate students on October 31, 2023. A retrospective chart review was conducted in March 31, 2025 to evaluate utilization of the template and extracted data was analyzed using descriptive statistics. The residents' feedback was collected during two focus-group sessions and analyzed qualitatively to assess their understanding of the importance of documentation, identify barriers to utilization of the template, and explore other alternatives for documentation.Results392 visit encounters on 250 patients were analyzed. Template utilization increased with time from graduated PGY-2 residents to current residents, but it was not universal or uniform. Qualitative analysis revealed that residents fully understand the importance of accurate record keeping, and the template's intended advantages. However, barriers for utilization like time constraints, difficulties when reporting multiple lesions in our complex patient population, and its accessibility within the system, limit their capabilities to comply.ConclusionAlthough a standardized electronic template can be an effective method of evaluating and documenting caries arrest in SDF-treated teeth, compliance with its use at every encounter is difficult in a hectic university clinic that treats very young children. Further investigation is required to overcome barriers for its use, and to test additional strategies that could be feasible in a dental educational setting.